Do different degrees of human activity affect the diet of Brazilian silverside Atherinella brasiliensis?. Issue 2 (22nd June 2016) - Alves, V. E. N.; Patrício, J.; Dolbeth, M.; Pessanha, A.; Palma, A. R. T.; Dantas, E. W.; Vendel, A. L.
Abstract : The aim of the present study was to test whether different degrees of human activity affect the diet of the Brazilian silverside Atherinella brasiliensis in two tropical estuaries. Fish were collected along the salinity gradient of two Brazilian estuaries, the heavily impacted Paraiba Estuary and the less impacted Mamanguape Estuary, in the dry and wet seasons. The findings confirm that A. brasiliensis has generalist feeding habits and is able to change its diet under different environmental conditions. The results indicate clear spatial ( i.e. along the estuarine gradient) changes in diet composition in both estuaries, but diet was also influenced by the degree of anthropogenic disturbance. During the wet season in the nutrient enriched Paraiba Estuary, when human activity was higher, the diet of A. brasiliensis was poorer and dominated by few dietary items, reflecting the potential impoverishment of prey items in this heavily disturbed system. The specimens collected in the most affected estuary also had a greater frequency of micro‐plastics and parasites in their stomachs, reflecting the greater degree of human disturbance in the estuary. The present findings suggest that the diet of A. brasiliensis could be a useful indicator of changes in the ecological quality of these and other tropical estuaries of the western Atlantic Ocean.